Physics for scientists & engineers with modern physics - Giancoli, Douglas C. (Pearson Prentice Hall, 2009)
Volume 1: Describing motion.- Kinematics. - Dynamics.- Newton's laws.-Work and energy.- Linear momentum.- Static equilibrium.- Fluids.- Oscilations.- Wave motion.- Sound.- Temperature.- Kinetic theory of gases.- Law of thermodynamics. Volume 2: Eletric charge and electric field.- Gauss' law.- Electric potential.- DC circuits.- Magnetism.- Sources of magnetic field.- Lenses and optical instruments.- Difraction and polarization.- Volume 3: Special theory of relativity. Quantum mechanics.- Molecules and solids. - Nuclear physics and radioactivity.- Elementary particles.- Astrophysics and cosmology. Appendices.